2017
DOI: 10.2136/vzj2016.06.0055
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Scaling of Vegetation Growth and Soil Formation: Explicit Predictions

Abstract: In a previous study, vegetation linear extent and soil depth as functions of time were proposed to follow percolation-based scaling laws of power-law form. Although the power-law exponents are specified by theory, the fundamental length, x 0 , and time, t 0 , scales must be generated from physical arguments. In principle, these length and time scales can vary widely with climate, soil, and plant variables. In the previous study, approximate values, microns and seconds, were proposed for x 0 and t 0 , based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 75 publications
0
48
0
Order By: Relevance
“…Progress has recently been made in this direction (Yu & Hunt, ), and the problem has been addressed more quantitatively, correcting two errors in existing calculations (Salehikhoo et al, ). More clearly even than the relevance to chemical weathering should be the relevance of solute transport to the formation of calcic and gypsic horizons. The relevance of percolation scaling of solute transport to the formation of such horizons in arid and semiarid regions was recently confirmed (Hunt, ; Hunt & Ghanbarian, ). The strong dependence of solute transport on length and timescales suggests the possibility that other phenomena, such as vegetation growth rates, may be also affected by the “edaphic” constraints of the soil. Evidence is accumulating that the exponent that characterizes 2‐D optimal paths describes the spatiotemporal scaling of vegetation growth, and that the variability across species, climates, and substrates can be attributed to variation in transpiration rates (Hunt, , ).…”
Section: Possible Future Directions For Application Of Percolation Thmentioning
confidence: 83%
See 2 more Smart Citations
“…Progress has recently been made in this direction (Yu & Hunt, ), and the problem has been addressed more quantitatively, correcting two errors in existing calculations (Salehikhoo et al, ). More clearly even than the relevance to chemical weathering should be the relevance of solute transport to the formation of calcic and gypsic horizons. The relevance of percolation scaling of solute transport to the formation of such horizons in arid and semiarid regions was recently confirmed (Hunt, ; Hunt & Ghanbarian, ). The strong dependence of solute transport on length and timescales suggests the possibility that other phenomena, such as vegetation growth rates, may be also affected by the “edaphic” constraints of the soil. Evidence is accumulating that the exponent that characterizes 2‐D optimal paths describes the spatiotemporal scaling of vegetation growth, and that the variability across species, climates, and substrates can be attributed to variation in transpiration rates (Hunt, , ).…”
Section: Possible Future Directions For Application Of Percolation Thmentioning
confidence: 83%
“…The relevance of percolation scaling of solute transport to the formation of such horizons in arid and semiarid regions was recently confirmed (Hunt, ; Hunt & Ghanbarian, ). The strong dependence of solute transport on length and timescales suggests the possibility that other phenomena, such as vegetation growth rates, may be also affected by the “edaphic” constraints of the soil. Evidence is accumulating that the exponent that characterizes 2‐D optimal paths describes the spatiotemporal scaling of vegetation growth, and that the variability across species, climates, and substrates can be attributed to variation in transpiration rates (Hunt, , ). The scaling hypotheses in vegetation growth and soil formation that were described earlier assume that the water that plants use—transpiration—drives vegetation growth, while the water that is not taken up by plants, or evaporated off the soil, or runs off the surface, but percolates through to the bottom of the soil layer, contributes to chemical weathering and soil formation.…”
Section: Possible Future Directions For Application Of Percolation Thmentioning
confidence: 83%
See 1 more Smart Citation
“…The theory of solute transport limited weathering ("percolation theory"; Hunt and Ghanbarian, 2016;Hunt, 2017;Yu et al, 2017) that explains the observed overall dependence of chemical weathering rates and soil formation on (1) time (or soil depth), (2) climate, i.e., the dominant influence on flow rates, (3) substrate heterogeneity scale, (4) erosion rates (thus relief), is based on a percolation theoretical treatment of solute transport. The erosion rate depends on the relief, or topography, and the time is expressed explicitly, thus accounting for all five of Dokuchaev's original soil forming factors.…”
Section: Relationship Of Chemical Weathering To Solute Transportmentioning
confidence: 99%
“…The solute velocity is obtained from a known scaling relationship between transit time and system length (Lee et al, 1999), plus the identification of the fundamental length and time scales (Hunt, 2017). The Damköhler number, Da I , which is the ratio (Salehikhoo et al, 2013) of a solute advection time to a reaction time under well-mixed conditions (Yu and Hunt, 2017a), measures the importance of solute transport relative to reaction kinetics on chemical weathering rates.…”
Section: Theory Solute Transport and Reaction Kinetics: Damköhler Numbermentioning
confidence: 99%